Effects of oxidative stress on the cardiac myocyte proteome: modifications to peroxiredoxins and small heat shock proteins. - Cullingford, T; Wait, R; Clerk, A; Sugden, P (2006)
Endogenous oxidative stress is a likely cause of cardiac myocyte death in vivo. We examined the early (0-2 h) changes in the proteome of isolated cardiac myocytes from neonatal rats exposed to H2O2 (0.1 mM), focussing on proteins with apparent molecular masses of between 20 and 30 kDa. Proteins were separated by two-dimensional gel electrophoresis (2DGE), located by silver-staining and identified by mass spectrometry. Incorporation of [35S]methionine or 32Pi was also studied. For selected proteins, transcript abundance was examined by reverse transcriptase-polymerase chain reaction. Of the 38 protein spots in the region, 23 were identified. Two families showed changes in 2DGE migration or abundance with H2O2 treatment: the peroxiredoxins and two small heat shock protein (Hsp) family members: heat shock 27 kDa protein 1 (Hsp25) and alphaB-crystallin. Peroxiredoxins shifted to lower pI values and this was probably attributable to 'over-oxidation' of active site Cys-residues. Hsp25 also shifted to lower pI values but this was attributable to phosphorylation. alphaB-crystallin migration was unchanged but its abundance decreased. Transcripts encoding peroxiredoxins 2 and 5 increased significantly. In addition, 10 further proteins were identified. For two (glutathione S-transferase pi, translationally-controlled tumour protein), we could not find any previous references indicating their occurrence in cardiac myocytes. We conclude that exposure of cardiac myocytes to oxidative stress causes post-translational modification in two protein families involved in cytoprotection. These changes may be potentially useful diagnostically. In the short term, oxidative stress causes few detectable changes in global protein abundance as assessed by silver-staining.